Piezoelectric response and figure of merit assessment in lead-free (Ba1-xSrx) (Zr0⋅025Ti0.975)O3 ceramics with low-level Sr2+ substitutions - Nor Amalina, Ahmad; Mohammad Hafizuddin, Jumali; Nor Huwaida, Janil Jamil; Nur Solehah, Ali; Zalita, Zainuddin (Elsevier Ltd., 2024)
This study investigates the effects of low-level Sr2+ substitutions on the microstructures and electrical properties of BSZT ceramics with formula (Ba1-xSrx)(Zr0⋅025Ti0.975)O3. The ability of BSZT ceramics to convert energy is assessed based on the piezoelectric coefficient, d33 associated with the figure of merit (FOM). BSZT ceramics with 0.00 ≤ x ≤ 0.10 were sintered at 1350 ◦C for 2 h. The XRD measurement confirmed the formation of a singlecrystalline phase in all ceramics. All ceramics stabilized in tetragonal crystal structures with progressive decline in tetragonality. It was found that the ceramic with low-level Sr2+ substitutions demonstrated excellent dielectric, piezoelectric and ferroelectric behaviours before gradually deteriorated at higher contents. Systematic deviation of Sr2+ atomic percentage signified broad dielectric curves compared to pristine Ba(Zr0⋅025Ti0.975)O3. A significant increase of remnant polarization, Pr value (11.21 ± 0.12 μC/cm2 ) was recorded when x = 0.02, in line with its highest as-sintered density and tetragonality. High d33 and low ε33 values contributed to an optimum value of piezoelectric voltage, g33 coefficient. Consequently, a high FOM comparable to PZT was obtained. The current work successfully demonstrated the preparation of lead-free ceramics based on BaTiO3 with great potential for energy conversion applications.